RUWA JURAI MODEL: THE INDONESIAN COASTAL VILLAGE LEGAL DESIGN - Budiyono (Faculty of Law-Universitas Bandar Lampung, 2022)
The sea coast in Indonesia is generally an area with high poverty, damaged ecology, low independence of rural social organizations and the loss of local cultural values, as well as poor infrastructure and health. Similar conditions were found along 1,105 km of coastal coastline in Lampung Province with an area of 16,625.3 km2 of coastal waters. This study aims to present the local wisdom of ruwa jurai in the legal arrangement of the Lampung sea coast. The results of the analysis concluded that the availability of legal instruments that protect and empower coastal communities with a socio-cultural religious aspect approach that integrates immigrants and natives in a spirit of togetherness into a long-term solution. Meanwhile, for the short term by implementing the law in the coastal area development policy in a single village development planning unit every year.